Implications of Organizational Culture, Servant Leadership, Competence on Quality of Work Life and Employee Performance Syar'i Garment - Eliza, Maria; Pratiwi, Nimas Aryany (LAA MAISYIR : Jurnal Ekonomi Islam, 2021)
In Surabaya, there is PT. X, which runs a syar'i garment SME business. The size of the area and the number of employees make this company have certain efforts to run its business. This study analyzes the influence of Organizational Culture, Servant Leadership, and Competence on Quality of Work Life and Employee Performance (Case Study of Syar'i Garment SMEs). This study uses a quantitative approach. The research hypothesis testing is carried out using a Structural Equation Model (SEM) based on Partial Least Square (PLS). The study results explain that organizational culture has a significant influence on the quality of work-life. Servant Leadership has no significant effect on the quality of work life, competence has a significant effect on the quality of work life, and organizational culture has a considerable impact on employee performance. Servant Leadership does not affect employee performance, competence has a significant effect on employee performance, and quality of work-life significantly affects employee performance.